2015
DOI: 10.1186/s40529-014-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Nostoc sp. extract induces oxidative stress-mediated root cell destruction in Mimosa pigra L.

Abstract: BackgroundMimosa pigra is an invasive weed in some regions of South East Asia and Australia. Our previous study has revealed that a cyanobacterium, Nostoc sp., extract can inhibit root growth in M. pigra seedlings. In this study, some physiological processes involve oxidative stress-mediated cell death and root ultrastructure were investigated to clarify the mechanisms of root growth suppression and bioherbicidal potential of the extract.ResultsNostoc sp. extract enhanced overproduction of reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Nostoc cells were cultured in BG11 medium, pH 6.5 at temperature of 32 ± 2°C, under daylight fluorescent lamps, light period of 14 light/10 dark [3].…”
Section: Cyanobacteria Culture and Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nostoc cells were cultured in BG11 medium, pH 6.5 at temperature of 32 ± 2°C, under daylight fluorescent lamps, light period of 14 light/10 dark [3].…”
Section: Cyanobacteria Culture and Extractionmentioning
confidence: 99%
“…The dried cells were ground to powder and extracted with 80 % methanol for 24 hours. The solution was centrifuged by 10,000 × g in 15 min to collect supernatant that was evaporated to obtain a crude brown gum [3].…”
Section: Cyanobacteria Culture and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPX activity was assayed by coupling the oxidation of glutathione to NADPH oxidation in the presence of t-butyl H2O2 as following the decrease in absorbance at 340 nm (Bagchi et al, 2012). The GR activity was determined according to Sukkhaeng et al (2015) by measuring the reduction of oxidized glutathione by quantifying NADPH oxidation at 340 nm. Cell free extract equivalent to 75 µg protein was used as the enzymatic source for all the aforementioned enzyme assays.…”
Section: Determination Of Enzymatic Antioxidantsmentioning
confidence: 99%
“…Extract of Nostoc sp. induced oxidative stress by accumulating reactive oxygen species (ROS), causing massive cell death in Mimosa pigra (Sukkhaeng et al 2015 ). Contrary, an in vitro study of Li and co-workers ( 2007 ) demonstrated that Nostoc species have their ability to scavenge ROS and inhibit lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%